Kynurenine administered together with probenecid markedly inhibits pentylenetetrazol-induced seizures. An electrophysiological and behavioural study - Németh H.; Robotka Hermina; Kis Zsolt; Rózsa Éva; Janáky Tamás; Somlai Csaba; Marosi Máté Gábor; Farkas Tamás; Toldi József; Vécsei László (Pergamon Press, 2004)
The kynurenine pathway converts tryptophan into various compounds, including L-kynurenine, which in turn can be converted to the excitatory amino acid receptor antagonist kynurenic acid, which may therefore serve as a protective agent in such neurological disorders as epileptic seizures. Kynurenic acid, however, has a very limited ability to cross the blood-brain barrier, whereas kynurenine passes the barrier easily. In this study, we tested the hypothesis that kynurenine administered systemically together with probenecid, which inhibits kynurenic acid excretion from the cerebrospinal fluid, results in an increased level of kynurenic acid in the brain that is sufficiently high to provide protection against the development of pentylentetrazol-induced epileptic seizures. CA3 stimulation-evoked population spike activity was recorded from the pyramidal layer of area CA1 of the rat hippocampus, and in another series of behavioural experiments, water maze and open-field studies were carried out to test the presumed protective effect of kynurenine + probenecid pre-treatment against pentylenetetrazol-induced seizures. This study has furnished the first electrophysiological proof that systemic kynurenine (300 mg/kg, i.p.) and probenecid (200 mg/kg, i.p.) administration protects against pentylenetetrazol-induced (60 mg/kg, i.p.) epileptic seizures. (C) 2004 Elsevier Ltd. All rights reserved.